Nest density as determinants for habitat utilizations of Bornean orangutan (Pongo pygmaeus wurmbii) in degraded forests of Gunung Palung National Park, West Kalimantan - DIDIK PRASETYO; JITO SUGARDJITO (Biodiversitas Journal of Biological Diversity, 2011)
Prasetyo D, Sugardjito J (2011) Nest density as determinants for habitat utilizations of Bornean orangutan (Pongo pygmaeus wurmbii) in degraded forests of Gunung Palung National Park, West Kalimantan. Biodiversitas 12: 164-170. Conversion of forests into nonforests areas particularly for the development of timber industry and oil palm plantation in Ketapang district, West Kalimantan province was drastically increased recently. We have conducted an assessment for the density of Bornean orangutans Pongo pygmaeus wurmbii L. in degraded forests of the boundary of Gunung Palung National Park, West Kalimantan in 2004 and 2005. We used line-transects nest-count to survey 39,6 km length at 13 sites including 7 in side the park and the other 6 situated out side the park which holds a difference status of forest management. The differences of nest density between degraded forests habitat was calculated. The olddegraded forest which has been logged for 5 years or more, were containing more new nests in a cluster compared to the recently as well as currently logged. The highest number of orangutan’s nests could be found in the old degraded forest in side the park, whereas the lowest one was obtained in the currently logged protection forest with the density of 3.70 ind/km2 and 0.06 ind/km2 respectively. We compare these results with the survey undertaken previously in the area when the logging and forest conversion activities have just begun in the region in 2001.